MODEL PENDEKATAN MANAJEMEN RISIKO - Bayu Wijayantini (Universitas Jember, 2012)
Risk has became as a complex phenomenon, and risk management clearly requires in other to business survival. This article attempt to describes some methodology approach for risk management implementation. There are three common extendable phases in risk management which is depend on their own condition and considerations. Key words: risk, management, identify, analysis